Cultural Sustainability: Sustaining Traditional Architecture for Tourism in Malaysia - a Case Study of Bangsar, Bukit Bintang and Sunway Lagoon Resort - S. Selvaratnam, Doris Padmini (2004)
The process of globalisation has both positive (technological advancement, bridging communities, breaking down cultural and political borders) and negative (eroding cultural values, creating standardised cities) impact on the lives of the society be it in the sphere of economy, politics, social or culture. The two most important facets of globalisation are the economy and culture. While the economic growth and development are manifested in terms of tourism development, the thrust of the tourism industry capitalises on the natural and cultural capital of a nation. A nation is greatly challenged to safeguard, preserve and conserve its cultural identity especially as it is also an asset in the tourism industry. The thrust of the thesis is based on the sustainable tourism development policy as advocated by WTO (1996) campaigning for equal power sharing relations between the local authority, private sector and the local community. The researcher relied on the triangulation method to obtain secondary and primary data. Interviews based on semi-structured and structured research schedules helped to obtain the qualitative and quantitative data from the government officers,local authority officials, private sector (tour and travel agents, hotel owners associations, and car rental associations) and the local community (local tourists, foreign tourists and non-governmental organisations). Data was processed and analysed using SPSS and content analysis methods. The findings indicate that the government plays a major role to shape the local traditional architectural landscape, especially at the study locations of Bangsar, Bukit Bintang and Sunway Lagoon Resort. While the private sector complemented with regular inputs and decorations at hotels, the local community did not play an active role in the planning or decision-making process. The locals were unhappy with the absence of local architectural designs at the study locations, but were satisfied with the presence of a well-managed and modern atmosphere. A suggestion for a Malaysian Sustainable Tourism Development Indicator was made incorporating the social and cultural elements.